Polimer Malzemelerde Sürtünme Kaynaklı Gürültü - Altınkaynak, Atakan (Fen Bilimleri Enstitüsü, 2015)
Teknikte kullanılan polimer malzemelerin çeşitli parametrelere bağlı olarak gürültü karakteristiklerinin belirlenebilmesi için bir pim-ring deney tesisatı kullanılmıştır. Deney tesisatında değiştirilebilen parametreler normal yük ve kayma hızıdır. Ölçülebilen büyüklükler ise sürtünme kuvveti ve tur sayısıdır. Ses ölçümü ise, yarım parmak mikrofon yardımıyla 1/3 oktav bandında 400 Hz ile 20 kHz arasındaki frekans bandında yapılmıştır. Ses ölçümü için ayrıca bir akustik oda tasarlanmıştır. Sistemde tahrik elemanı olarak 0...800 d/dak arasında ayarlanabilen bir AC motor kullanılmıştır. Sistemde normal kuvvet, yük koluna asılan ölü ağırlıklar yardımıyla uygulanmaktadır. Sürtünme kuvveti ise, sabit diske yerleştirilmiş 0,1 N hassasiyetinde bir kuvvet transdüseri yardımıyla ölçülmektedir. Deneylerde grafit katkılı döküm poliamid 6, MoS2 katkılı döküm poliamid 6, MoS2 katkılı poliamid 66 ve saf poliamid 6 kullanılmıştır. Ses basınç düzeyi ölçümleri, 45 N’ luk sabit normal yük altında, 0,2 m/sn, 0,5 m/sn ve 1 m/sn olmak üzere üç farklı hızda gerçekleştirilmiştir. Sonuç olarak, ses basınç düzeyinin genel olarak kayma mesafesi ile değişmediği, 1/3 oktav bandındaki düşük merkez frekans değerleri için artan hızla bir miktar arttığı görülmüştür. Ayrıca sürtünme katsayısının yüksek olduğu durumlarda sürtünme kaynaklı titreşimin gürültüyü önemli ölçüde arttırıcı yönde etki yaptığı görülmüştür.

A pin on ring test apparatus has been utilized to analyze the noise characteristics of polymers used especially in industry under various operating conditions. Adjustable parameters are normal load (surface pressure) and sliding speed. Frictional force and number of revolution are the parameters recorded during the experiments. The frictional noise generated by the polymer-steel contact is monitored by the ½ microphone. The sound pressure level is analyzed in the range from 400 Hz to 20 kHz frequency in 1/3 octave spectra. Also, an acoustic chamber is designed for noise measurements. The system was driven by an AC motor having 0...800 rpm variable speed range. The normal load was applied by dead weights hanging on the loading arm. The frictional force was measured with a force transducer with 0,1 N in accuracy placed on the pin holder. Graphite reinforced cast polyamide 6, MoS2 reinforced cast polyamide 6, MoS2 reinforced polyamide 66 and polyamide 6 are used in experiments. Sound pressure level measurements are carried out for three different speeds 0,2 m/s, 0,5 m/s and 1 m/s under 45 N normal load. It is concluded that sound pressure level generally does not vary with the sliding distance whereas it slightly increases with the sliding speed in the low center frequencies of 1/3 octave bands. Moreover, in the cases where the coefficient of friction is relatively high, friction induced vibration has a significant effect on the increase of sound pressure level.
Friction Induced Noise In Polymers
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2005
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2005
Keywords: sürtünme; gürültü; polimer; friction; noise; polymer